2001
DOI: 10.1128/jvi.75.10.4832-4842.2001
|View full text |Cite
|
Sign up to set email alerts
|

Selective Excision of AZTMP by Drug-Resistant Human Immunodeficiency Virus Reverse Transcriptase

Abstract: Two distinct mechanisms can be envisioned for resistance of human immunodeficiency virus type 1 (HIV-1) reverse transcriptase (RT) to nucleoside analogs: one in which the mutations interfere with the ability of HIV-1 RT to incorporate the analog, and the other in which the mutations enhance the excision of the analog after it has been incorporated. It has been clear for some time that there are mutations that selectively interfere with the incorporation of nucleoside analogs; however, it has only recently been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
358
4
7

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(383 citation statements)
references
References 24 publications
14
358
4
7
Order By: Relevance
“…RT containing thymidine analog mutations (TAMs) shows an increased capacity to unblock AZT-MP-terminated primers in the presence of physiological concentrations of ATP (3,21). Since the K70E mutation reduced the ability of RT to excise AZT-MP, we hypothesized that this mutation may antagonize excision by TAMs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RT containing thymidine analog mutations (TAMs) shows an increased capacity to unblock AZT-MP-terminated primers in the presence of physiological concentrations of ATP (3,21). Since the K70E mutation reduced the ability of RT to excise AZT-MP, we hypothesized that this mutation may antagonize excision by TAMs.…”
Section: Resultsmentioning
confidence: 99%
“…HIV-1 RT has the innate capacity to unblock NRTI-MPterminated primers in the presence of physiological concentrations of ATP or PPi (1,22). Biochemical studies show that TAMs confer resistance to AZT and other NRTI by accelerating the rate at which the terminal AZT-MP (or other NRTI-MP) is removed through phosphorolytic cleavage (3,21). Both the K65R (this study; 25,29,35) and K70E (this study) mutant enzymes exhibit rates of ATP-or PPi-mediated phosphorolytic excision that are either significantly reduced or similar (in the case or PPi) to the WT enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Previous biochemical studies have shown that the incorporated chain terminator can be removed from the primer terminus through phosphorolytic cleavage in the presence of either pyrophosphate (PP i ) (1) or in the presence of ribonucleotide triphosphates (NTPs) (2), which were shown to act as pyrophosphate donors. Increasing evidence suggests that the latter reaction pathway provides an important mechanism for HIV resistance to AZT and, to a certain degree, also to other NRTIs (3)(4)(5)(6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…Resistance against AZT-TP was attributed to two distinct mechanisms (Clavel and Hance, 2004;Boyer et al, 2001;Ray et al, 2003): (i) excision of AZT-TP from the DNA chain, and (ii) decrease in affinity of RT to AZT-TP. Both processes can be incorporated into our effect model by increasing K m .…”
Section: Discussionmentioning
confidence: 99%
“…HIV develops resistance against zidovudine by two distinct mechanisms: (i) lowering the affinity of AZT-TP to RT, and (ii) enhancing the ATP-dependent excision of incorporated AZT-TP (Clavel and Hance, 2004;Boyer et al, 2001;Ray et al, 2003). In terms of our mechanistic effect model, both processes can be accounted for by increasing K RT m,TP .…”
Section: The Impact Of Resistance Mutationsmentioning
confidence: 99%